Heliopolis, Funde aus der Nekropole von Ard Neqabet El-Muhamin (1987–88) - Wagdy, Abdelghaffar (Zeitschrift für ägyptische Sprache und Altertumskunde, 2024)
The modern settlements of El-Matariya and Ain Shams are located to the north-east of Cairo, now covering the cemetery of Heliopolis. This necropolis contained many tombs from the Old Kingdom, or even before, which continued to be in use through the Late Period (7th–4th centuries BC). Heliopolis is considered one of the oldest religious cities in the history of ancient Egypt, which has not been systematically and fully excavated. During the rescue excavations of Ard Neqabet El-Muhamin in Ain-Shams East (Heliopolis) in 1987–8, many objects were found. They come from different periods, have different shapes and have been made from different materials. The aim of this research is to study in detail the objects, which stem from the excavations of Ard Neqabet El-Muhamin at Heliopolis which they are kept in El-Matariya’s storerooms and Grand Egyptian Museum, which have not been published completely. These objects have a lot of archaeological information, which need to be published in scientific research, to help date these artifacts and cast light on them. تقع منطقه المطرية وعين شمس الحالية شمال شرق القاهرة، فوق جبانة هليوبوليس. احتوت هذه الجبانة على العديد من المقابر من عصر الدولة القديمة، والتي استمرت في الاستخدام خلال الفترة المتأخرة. تعتبر هليوبوليس واحدة من أقدم المدن الدينية في تاريخ مصر القديمة، والتي لم يتم التنقيب عنها بشكل منهجي وكامل. أثناء حفائر الإنقاذ في أرض نقابة المحامين في عين شمس الشرقية (هليوبوليس) تم العثور على العديد من اللقى الأثرية من فترات زمنيه مختلفة. الهدف من هذا البحث هو الدراسة التفصيلية لهذه لقطع والتي تم حفظها في مخازن المطرية والمتحف المصري الكبير، والتي لم يتم نشرها من قبل، حيث تحتوي هذه اللقى على الكثير من المعلومات الأثرية، والتي يجب نشرها في بحث علمي، للمساعدة في تحديد تاريخ هذه القطع الأثرية وإلقاء الضوء عليه.